Expert opinion on the clinical use and benefits of liposomal iron in the treatment of anemia in Indian settings - S., Manjula; M., Krishna Kumar (International Journal of Research in Medical Sciences, 2024)
Background: Several studies have reported the effectiveness and safety of liposomal iron in increasing hemoglobin levels and correcting anemia. However, there was a dearth of information regarding the prescription pattern of physicians regarding its use and advantages in the actual practice. The present survey-based study aims at gathering clinicians’ perspectives regarding the clinical use and benefits of liposomal iron in the treatment of anemia in Indian settings. Methods: This cross-sectional study used a 19-item questionnaire to gather insights from specialists across different Indian settings regarding their perspectives on anemia and liposomal iron. Results: Out of 124 participants, 77% opined that liposomal iron was highly bioavailable, achieves much higher plasma iron concentration, and bypasses the extremely restrictive, normal intestinal barriers. Oral liposomal iron was preferred by 77% of clinicians for the rapid increase in hemoglobin level and 99% of clinicians reported improved patient compliance with liposomal iron therapy for anemia. According to 50% of clinicians, oral liposomal iron was effective in non-hemodialysis dependent chronic kidney diseases and 87% of clinicians reported that patients without CKD needed oral liposomal iron. Half of the respondents reported a significant increase in Hb with liposomal iron in both dialysis and non-dialysis patients. Conclusions: The survey participants reported that liposomal iron treatment for anemia was beneficial in treating both CKD and non-CKD patients. The survey findings have corroborated the advantages of liposomal iron for treating anemia such as increased bioavailability, rapid and effective increase in Hb level, better patient compliance and tolerability, decreased side effects, cost-effectiveness, and flexible dosing.